Rapid Synthesis of Taxifolione and Taxifolial D, Two Metabolites from the Marine Alga Caulerpa taxifolia - Fecourt, Fabien; Carlier, Cedric; Pale, Patrick (Letters in Organic Chemistry, 2009)
The synthesis of two natural products - Taxifolione and Taxifolial D - isolated from the marine alga Caulerpa taxifolia invading the Mediterranean Sea was performed. Coupling reactions allowed for a rapid synthesis. The surprising Z configuration of Taxifolial D was confirmed after synthesis and comparison of each synthetic stereoisomer.
Keywords: antitumor agents